Circular Economy Cultivation Project to Create Young Entrepreneurs for Students from Remote Areas (3T) - Franky Boentolo; Hanjaya Siaputra (Jurnal Pengabdian Sains dan Humaniora, 2025)
Entrepreneurship rate in Indonesia is relatively low, comparing with neighboring countries in ASEAN. Meanwhile, entrepreneurship rate is a crucial factor to support the development of a country. Indonesia needs a lot of new entrepreneurship, especially in provinces outside Java, more specifically in areas classified as underdeveloped, frontier, and outermost (3T). Creating new entrepreneurs from these 3T areas is important. With this entrepreneurial program, these young talents will be able to obtain and apply their entrepreneurial skills. When they finish their study period, they are expected to return to their respective areas of origin. The entrepreneurship development program is carried out by involving them in aquaponic cultivation projects that apply circular economy principles. This concept was chosen because due to its broad application, as well as optimizing revenue through process efficiency. The students were involved as daily managers to understand the cultivation process model. They are also given the role of managing business concepts, both in terms of product sales and business concept development. As long as they involved, they are also guided by mentors, both in the spiritual aspect, as well as the leadership aspect. Due to this involvement, these students will be optimized and master the business model.